Validating the Influence of Effective Communication, Team Competency and Skills, Active Leadership on Construction Risk Management Practices of Nigerian Construction Companies - Adeleke, A. Q.; Windapo, Abimbola Olukemi; M., Waris; Bamgbaded, J. A.; Salimon, Maruf Gbadebo; Nawanir, Gusman (Academic Research Publishing Group, 2018)
he purpose of stressing the importance of risk management among construction companies is to reduce the effects of risk on projects and make the construction activities more profitable, completed to quality standards, time and budget. This significant deliberation has stimulated various research interests by construction companies, specifically viewing the risk in construction activities that affect project performance; (time overrun, cost overrun and low quality) as the significant risks attached to the projects from the global point of view. Using Partial Least Squares- Structural Equation Modeling approach, this study validates construction risk management (CRM) as a construct from the perspectives of 238 local, national and multi-national construction companies in Nigeria. A cross-sectional survey was conducted where data was gathered from companies through a structured questionnaire. Findings from this study disclosed that effective communication, team competency and skills with active leadership have a significant influence on construction risk management (CRM) practices of the Nigerian construction companies.